ChemInform Abstract: Geminal Bis(silyl) Enal: A Versatile Scaffold for Stereoselective Synthesizing C3, O1‐Disilylated Allylic Alcohols Based upon Anion Relay Chemistry. Issue 26 (6th June 2013) - Yan, Linjie; Sun, Xianwei; Li, Hongze; Song, Zhenlei; Liu, Zengjin
Abstract Geminal bis(silyl) enal (I) is shown to be a useful scaffold for anion relay chemistry (ARC) aimed at the stereoselective synthesis of trisubstituted vinylsilanes.